Ground-based observation of the cyclic nature and temporal variability of planetary-scale UV features at the Venus cloud top level - Imai, Masataka; Takahashi, Yukihiro; Watanabe, Makoto; Kouyama, Toru; Watanabe, Shigeto; Gouda, Shuhei; Gouda, Yuya (Icarus (New York, N.Y. 1962), 2016)
•Continuous ground-based Venus observations were conducted monitoring the annual phenomena on Venus.•Variabilities in the propagation periodicity of the UV feature on a planetary scale can be confirmed.•The prevailing first significant mode seems to change from 5.2-day waves to 3.5-day waves in about nine months.•During the transition periods of dominant-wave changing, the deformation of the Y-shaped UV feature is suggested. A planetary-scale bright and dark UV feature, known as the “Y-feature,” rotates around Venus with a period of 4–5 days and has been long-time interpreted as planetary waves. When assuming this, its rotation period and spatial structure might help to understand the propagation of the planetary-scale waves and find out their role in the acceleration-deceleration of the zonal wind speed, which is essential for understanding the super-rotation of the planet. The rotation period of the UV feature varied over the course of observation by the Pioneer Venus orbiter. However, in previous explorations of Venus such as Pioneer Venus and Venus Express, the spacecraft were operated in nearly fixed inertial space. As a result, the periodicity variations on sub-yearly timescales (one Venusian year is ∼224 Earth days) were obscured by the limitations of continuous dayside observations. We newly conducted six periods of ground-based Venus imaging observations at 365nm from mid-August 2013 to the end of June 2014. Each observation period spanned over half or one month, enabling long-term monitoring of Venus’ atmosphere above the equator region. Distributions of the relative brightness were obtained from the equatorial (EQ) to mid-latitudinal regions in both hemispheres, and from the cyclical variations of these distributions we deduced the rotation periods of the UV features of the cloud tops brightness. The relative brightness exhibited periods of 5.2 and 3.5 days above 90% of significance. The relative intensities of these two significant components also seemed subject to temporal variations. Although the 3.5-day component considered persists throughout the observation periods, its dominance over the longer period varied in a cyclic fashion. The prevailing first significant mode seems to change from 5.2-day waves to 3.5-day waves in about nine months, which is clearly inconsistent with the Venusian year. Clear periodic perturbations, indicating stability of the planetary-scale UV-feature, were observed only in the presence of single longer or shorter periodic waves. During the transition periods of dominant-wave changing, the amplitude of the relative brightness was largely changed. This can be explained by the deformation of the Y-shaped UV feature as observed by Pioneer Venus in 1979.